2005
DOI: 10.1111/j.1365-2567.2005.02239.x
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of systemic tolerance elicited by antigen inoculation into the vitreous cavity: vitreous cavity‐associated immune deviation

Abstract: SummaryThe immune privilege that exists in the eye is maintained by various mechanisms. One of the best studied is a form of systemic tolerance termed anterior chamber-associated immune deviation (ACAID). We have investigated the mechanisms by which ocular inflammation associated with the vitreous cavity (VC) is reduced, by injecting either ovalbumin (OVA) or allogeneic splenocytes into the VCs of mice, and assessed the effect of this on delayed type hypersensitivity (DTH) responses. After antigen inoculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 30 publications
0
48
0
2
Order By: Relevance
“…It is now known that the vitreous and subretinal space are also IP sites 107 and that antigens placed in these sites can even lead to the induction of an ACAID-like response. 22,54,55 In this context, it is interesting to note that (in mice) IP disruption occurs when RPE cells are damaged by laser burns. 18 This finding has raised the troubling question of whether laser-treated eyes are at increased risk of ocular inflammation, up to the collapse of eye IP.…”
Section: Ip and The Posterior Segment Of The Eyementioning
confidence: 99%
“…It is now known that the vitreous and subretinal space are also IP sites 107 and that antigens placed in these sites can even lead to the induction of an ACAID-like response. 22,54,55 In this context, it is interesting to note that (in mice) IP disruption occurs when RPE cells are damaged by laser burns. 18 This finding has raised the troubling question of whether laser-treated eyes are at increased risk of ocular inflammation, up to the collapse of eye IP.…”
Section: Ip and The Posterior Segment Of The Eyementioning
confidence: 99%
“…In other words, antigen injected into the anterior chamber [2], vitreous [3] or sub-retinal space [4] induces peripheral tolerance to that antigen. Furthermore, parts of the eye like the cornea are considered to be intrinsically immune privileged tissues because when transplanted to sites perfectly capable of rejecting foreign antigens, they enjoy acceptance.…”
Section: Regional Specialization Of Immune Responsesmentioning
confidence: 99%
“…1 Recently, it has been suggested that they are involved in 'vitreous cavity-associated immune deviation'. 2 Despite our considerable knowledge of the composition and structure of the vitreous humour, its physiological functions remain unclear. There is evidence that it regulates eye growth and shape during development.…”
Section: Introductionmentioning
confidence: 99%